In Vivo Metabolism of Aristolochic Acid I and II in Rats Is Influenced by Their Coexposure - Dedı Ková, Alena; Bárta, František; Martínek, Václav; Kotalík, Kevin; Dušková, Šárka; Mráz, Jaroslav; Arlt, Volker Manfred; Stiborová, Marie; Hodek, Petr (Chemical research in toxicology, 2020)
The plant extract aristolochic acid (AA), containing aristolochic acid I (AAI) and II (AAII) as major components, causes aristolochic acid nephropathy and Balkan endemic nephropathy, unique renal diseases associated with upper urothelial cancer. Differences in the metabolic activation and detoxification of AAI and AAII and their effects on the metabolism of AAI/AAII mixture in the plant extract might be of great importance for an individual's susceptibility in the development of AA-mediated nephropathies and malignancies. Here, we investigated in vivo metabolism of AAI and AAII after ip administration to Wistar rats as individual compounds and as AAI/AAII mixture using high performance liquid chromatography/electrospray ionization mass spectrometry. Experimental findings were supported by theoretical calculations using density functional theory. We found that exposure to AAI/AAII mixture affected the generation of their oxidative and reductive metabolites formed during Phase I biotransformation and excreted in rat urine. Several Phase II metabolites of AAI and AAII found in the urine of exposed rats were also analyzed. Our results indicate that AAI is more efficiently metabolized in rats in vivo than AAII. Whereas AAI is predominantly oxidized during in vivo metabolism, its reduction is the minor metabolic pathway. In contrast, AAII is mainly metabolized by reduction. The oxidative reaction only occurs if aristolactam II, the major reductive metabolite of AAII, is enzymatically hydroxylated, forming aristolactam Ia. In AAI/AAII mixture, the metabolism of AAI and AAII is influenced by the presence of both AAs. For instance, the reductive metabolism of AAI is increased in the presence of AAII while the presence of AAI decreased the reductive metabolism of AAII. These results suggest that increased bioactivation of AAI in the presence of AAII also leads to increased AAI genotoxicity, which may critically impact AAI-mediated carcinogenesis. Future studies are needed to explain the underlying mechanism(s) for this phenomenon.
Keywords: Chromatography, High Pressure Liquid; krysa rodu Rattus; teorie funkcionálu hustoty; hmotnostní spektrometrie s elektrosprejovou ionizací; kyseliny aristolochové; Male; Density Functional Theory; Animals; Rats, Wistar; Rats; mužské pohlaví; injekce intraperitoneální; Injections, Intraperitoneal; potkani Wistar; Spectrometry, Mass, Electrospray Ionization; zvířata; Aristolochic Acids; vysokoúčinná kapalinová chromatografie